TEKNO-KONOMI: BROADBAND INTERNET SEBAGAI STRATEGI PERTUMBUHAN INVESTASI DAN PENINGKATAN KESEJAHTERAAN MASYARAKAT INDONESIA - Siti Aminah Caniago; Feni Fitriani Putri Rozi; Bagaskara Sagita Wijaya (Wahana Islamika: Jurnal Studi Keislaman, 2022)
This study will examine the impact of using broadband internet networks on two sectors of economic growth, namely: Foreign Direct Investment, and the social welfare of the people in Indonesia by the provisions of the Human Development Index from the United Nations, by restructuring the economic sector through the implementation of research and development, innovation, and other factors strengthen economic digitization in Indonesia and describe upgrading steps to realize economic digitization in Indonesia. Using qualitative data and qualitative descriptive analysis methods, the researchers analyzed the development, potential, and role of the Internet in the development of the digital economy. The observation and recapitulation system of online investment transactions, online journals, books, papers, and other publications were used to obtain data in this study. As a result of this research, the challenge of economic digitization in Indonesia is the ability of the Indonesian people to adapt to new technologies and the diversity of locality values ​​in Indonesia which are still common. The strategy that can be applied is to develop various infrastructures that support internet connections and strengthen digital economic development governance that maintains the value of the Indonesian locality by involving various parties through collaborative steps. the use of the internet will provide different economic benefits for a country, depending on the level of income of the country. In conclusion, the digital economy in Indonesia must include improving economic processes and investment through technological innovation, encouraging growth through government regulations, and involving new actors in society as the foundation of economic growth and people's welfare.